Impact of the London 2012 Olympic and Paralympic Games on the personal and professional development of pharmacy volunteers. Issue 2 (30th May 2014) - File, Hayley; Mottram, David; Stuart, Mark; Thomas, Trudy
Abstract : Objectives: This study aimed to evaluate the impact and legacy of pharmacists' professional development having worked as volunteers at the London 2012 Olympic and Paralympic Games. Methods: Questionnaires were administered immediately following the Games and 1 year after the Games. The first explored motivation for volunteering, training and support and reflection on personal experiences at the time of the Games. The second evaluated the personal and professional impact that working as a volunteer has had in the year following the Games. Results: Immediately post-Games, 19 of the 22 (86.5%) respondents reported that they were able to use their pre-Games education and training effectively, particularly relating to antidoping regulations. One year after the Games, respondents reported that the experience had been influential on core aspects of their practice. Close collaboration with pharmacy colleagues, other healthcare professionals and Olympic and Paralympic team doctors was reported as a significant benefit of working at the Games. Conclusions: Comprehensive education and training is beneficial in providing a safe and efficient medicine service for athletes and provides a lasting legacy in terms of improving the standard of care for athletes or people participating in sport.